Method for efficiently preparing high-catalytic-performance biochar based on pulping black liquor and application
By adding a mixed solution of sodium hydroxide and sodium sulfide and ferric chloride hexahydrate to the pulping black liquid for heating and pyrolysis, sulfur-doped nano zero-valent iron biochar was prepared, which solved the problems of low lignin recovery rate and insufficient biochar function in the pulping black liquid, achieving efficient recycling and high-value conversion, and having excellent catalytic performance.
Patent Information
- Application Number
- CN202411837951.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing methods cannot simultaneously achieve efficient recovery of lignin and excellent functional biochar conversion in pulping black liquor.
By placing the waste biomass in a mixed solution of sodium hydroxide and sodium sulfide at high temperature, a black liquid was obtained, and then ferric chloride hexahydrate was added for heating reaction, and high-temperature pyrolysis was performed after freeze-drying to prepare sulfur-doped nano zero-valent iron biochar.
The efficient recycling and high-value conversion of lignin in pulping black liquor is achieved. The prepared biochar has better catalytic characteristics, which can effectively degrade antibiotic wastewater, reduce environmental pollution and reduce treatment costs.
Smart Images

Figure CN119680579A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of high-value conversion and application of waste biomass, and specifically relates to a method and application of efficiently preparing biochar with high catalytic performance based on pulping black liquor. Background Art
[0002] Waste biomass resources are large in quantity and contain high wood fiber content, and are often used in the papermaking and pulping industry. The use of chemical methods such as the sulfate method and the caustic soda method is one of the commonly used processes for papermaking and pulping. In the process of chemical pulping, a large amount of pulping black liquor by-products will be produced. As a biomass waste, this type of black liquor has a large output and is difficult to degrade, which poses great difficulties for the factory's treatment. Not only does it increase the processing cost, it also brings certain environmental pollution. Studies have shown that chemical pulping black liquor contains a large amount of lignin. As we all know, lignin is a biomass energy source and a high-molecular organic matter with excellent structural characteristics and high product value. Therefore, how to efficiently separate and recover lignin in black liquor to achieve harmless treatment and high-value conversion of pulping black liquor has become the key to research.
[0003] At present, the main focus of the separation and extraction of lignin in black liquor is on the extraction purity of lignin to produce biomass energy and high value-added fuel products. However, under the condition of paying attention to the separation and purification of lignin, it is easy to cause the problem of low lignin recovery yield, and the cumbersome separation and extraction process increases the cost of treatment. The acid precipitation method is one of the traditional mature methods for separating lignin. The process is simple, but the wastewater treatment technology after the implementation of this process is also a difficult problem. Therefore, some studies have used ferric chloride and sodium hydroxide to co-precipitate lignin, and then carbonized it into nano zero-valent iron biochar in one step to achieve the modification, capture and high-value conversion of lignin without damaging the quality of lignin. However, although this method achieves efficient and convenient recovery of lignin in black liquor, the functionality of the resulting biochar is still insufficient and needs to be improved. Summary of the invention
[0004] The purpose of the present invention is to solve the technical problem that the existing methods cannot simultaneously achieve efficient recovery of lignin in pulping black liquor and conversion of biochar with excellent functionality, and to provide a method and application for efficiently preparing biochar with high catalytic performance based on pulping black liquor.
[0005] The technical solution of the present invention is as follows:
[0006] One of the purposes of the present invention is to provide a method for efficiently preparing biochar with high catalytic performance based on pulping black liquor, the method being carried out according to the following steps:
[0007] S1: placing the waste biomass in a mixed solution of sodium hydroxide and sodium sulfide and heating it at high temperature to separate the solid and liquid to obtain black liquor;
[0008] S2: Add ferric chloride hexahydrate to the black liquor, heat for reaction, freeze-dry the precipitate after centrifugation, and then pyrolyze it at high temperature in a tubular furnace to obtain sulfur-doped nano zero-valent iron biochar.
[0009] It is further defined that the waste biomass in S1 is straw, wood or livestock and poultry manure.
[0010] It is further defined that the concentration of sodium hydroxide in the mixed solution in S1 is 0.5-1.5 mol / L.
[0011] It is further defined that the molar ratio of sodium hydroxide to sodium sulfide in S1 is (4-6):1.
[0012] It is further defined that the ratio of waste biomass to mixed solution in S1 is 1 g: (15-25) mL.
[0013] It is further defined that the high temperature heating in S1 is performed at a temperature of 110-130° C. and a time of 1.5-2.5 h.
[0014] It is further defined that the concentration of ferric chloride hexahydrate in the black liquor in S2 is 0.40-0.5 mol / L.
[0015] It is further defined that the heating temperature in S2 is 50-70° C. and the heating time is 0.5-1.5 h.
[0016] It is further defined that the temperature of high temperature pyrolysis in S2 is 650-750°C and the time is 1-3h.
[0017] The second object of the present invention is to provide an application of the above method in the high-value conversion of pulping black liquor.
[0018] The third object of the present invention is to provide a biochar prepared according to the above method.
[0019] A fourth object of the present invention is to provide an application of the biochar prepared by the above method in the field of water treatment.
[0020] A fifth object of the present invention is to provide a method for advanced oxidation treatment of antibiotic wastewater, wherein:
[0021] The antibiotic wastewater was treated using the above-mentioned sulfur-doped nano zero-valent iron biochar catalytic oxidant at room temperature.
[0022] Further limiting, the antibiotics include sulfamethoxazole and sulfamethoxazole.
[0023] It is further defined that the antibiotic concentration in the wastewater is 5-15 mg / L.
[0024] It is further defined that the oxidant comprises peroxymonosulfate, and the amount of the oxidant used is 0.5-5 mmol / L.
[0025] It is further defined that the biochar dosage is 0.35-0.45 g / L.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] The present invention is aimed at preparing high-value products after separating and recovering lignin, adopts corresponding means to precipitate lignin and endow it with product conversion potential, makes full use of the sulfur element in black liquor, introduces other metal elements, and further obtains biochar with excellent functionality by optimizing process parameters. The specific advantages are as follows:
[0028] (1) The present invention provides a method for efficiently recovering lignin from black liquor produced during the kraft chemical pulping process, which has the advantages of simple operation steps and high recovery rate compared to traditional methods. The method can not only recover lignin, but also precipitate sulfur in the black liquor at the same time. At the same time, by optimizing the process parameters, the biochar converted to high value has both heteroatom sulfur and transition metal iron, which gives the biochar better catalytic properties.
[0029] (2) The present invention simultaneously realizes the efficient recovery and high-value conversion of lignin in the black liquor produced by chemical pulping. The treatment and utilization of black liquor reduces environmental pollution and greatly reduces the cost of treating such difficult-to-biodegrade water bodies. The high-value conversion biochar of black liquor is applied to the catalytic degradation of sulfonamide antibiotic wastewater, reflecting the ecological concept of treating waste with waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The concentration of the remaining lignin in the liquid after the lignin was separated and precipitated in Examples 1-2 and Comparative Examples 1-3; ↑ represents the increase in the extraction rate compared with Comparative Example 1;
[0031] Figure 2 is the concentration of residual iron ions in the liquid after precipitating lignin in Examples 1-2 and Comparative Examples 2-3;
[0032] Figure 3 The yield of biochar prepared in Examples 1-2 and Comparative Examples 2-3;
[0033] Figure 4 Comparison of chemical element contents of biochars prepared in Examples 1-2 and Comparative Examples 1-3;
[0034] Figure 5 X-ray diffraction (XRD) patterns of the biochars prepared in Examples 1-2 and Comparative Examples 2-3;
[0035] Figure 6 This is a high-resolution transmission electron microscopy (HRTEM) morphology image of the biochar prepared in Example 2;
[0036] Figure 7 The X-ray diffraction (XRD) pattern of the biochar prepared in Comparative Example 4;
[0037] Figure 8 The X-ray diffraction (XRD) pattern of the biochar prepared in Comparative Example 5;
[0038] Fig. 9 This is the degradation behavior diagram of sulfamethoxazole degraded by peroxymonosulfate activated by different biochars in the application example;
[0039] Fig.10 This is the degradation behavior diagram of sulfamethazine degrading by peroxymonosulfate activated by different biochars in the application example. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0041] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0042] Embodiment 1:
[0043] The method for efficiently preparing biochar with high catalytic performance based on pulping black liquor in this embodiment is carried out in the following steps:
[0044] (1) Add 5 g corn stalks (40-100 mesh) to 100 mL of a mixed solution of 1 mol / L sodium hydroxide and 0.2 mol / L sodium sulfide nonahydrate, heat in a constant temperature oil bath at 120°C at normal pressure for 2 h, and vacuum filter to separate the solid and liquid to obtain pulping black liquor. The lignin concentration in the black liquor is 100% (see attached). Figure 1 shown), as a control for the efficiency of lignin precipitation at a later stage.
[0045] (2) Take 20 mL of the pulping black liquor obtained in step (1), add ferric chloride hexahydrate thereto according to the concentration of ferric chloride hexahydrate in the black liquor of 0.40 mol / L, react at 60° C. for 60 min, and retain the supernatant obtained by the first centrifugation after the reaction, which is recorded as 0.40F. The precipitate after the first centrifugation is washed and centrifuged three times, and then freeze-dried as the raw material for preparing subsequent biochar.
[0046] (3) The precipitate obtained in step (2) was pyrolyzed at 700° C. for 2 h in a tube furnace and naturally cooled to room temperature to obtain sulfur-doped iron-based biochar, recorded as 0.40 FLC.
[0047] Embodiment 2:
[0048] The difference between this embodiment and embodiment 1 is that the concentration of ferric chloride hexahydrate in the black liquor in step (2) is 0.46 mol / L, and the supernatant obtained by the first centrifugation after the reaction is retained and recorded as 0.46F. The biochar obtained in step (3) is recorded as 0.46FLC. The other steps and parameters are the same as those in embodiment 1.
[0049] Comparative Example 1:
[0050] The difference between this comparative example and Example 1 is that: in step (1), lignin is recovered by precipitation using the traditional hydrochloric acid method, specifically, the sodium hydroxide / sodium sulfide nonahydrate mixed solution is replaced by hydrochloric acid solution, the pH is adjusted to 1.8 by adding hydrochloric acid solution, and the precipitate is freeze-dried and directly subjected to step (3), and the obtained biochar is recorded as LC. The other steps and parameters are the same as those in Example 1.
[0051] Comparative Example 2:
[0052] The difference between this comparative example and Example 1 is that the concentration of ferric chloride hexahydrate added in step (2) is 0.55 mol / L, and the supernatant obtained by the first centrifugation after the reaction is retained and recorded as 0.55F. The biochar obtained in step (3) is recorded as 0.55FLC. The other steps and parameters are the same as those in Example 1.
[0053] Comparative Example 3:
[0054] The difference between this comparative example and Example 1 is that the concentration of ferric chloride hexahydrate added in step (2) is 0.65 mol / L, and the supernatant obtained by the first centrifugation after the reaction is retained and recorded as 0.65F. The biochar obtained in step (3) is recorded as 0.65FLC. The other steps and parameters are the same as those in Example 1.
[0055] Comparative Example 4:
[0056] (1) 5 g corn stalks (40-100 mesh) were mixed with 100 mL of a 2 wt% hydroxide solution, heated at 75° C. in an oil bath at atmospheric pressure for 120 min, and vacuum filtered to separate the solid and liquid. The resulting liquid was biomass black liquor;
[0057] (2) adding ferric chloride hexahydrate to the biomass black liquor obtained in step (1), the ratio of biomass black liquor to ferric chloride hexahydrate being 20 mL:1 g, heating the mixture at 60° C. for 60 min, centrifuging to obtain a precipitate, washing the precipitate three times with ultrapure water, and drying the precipitate to a constant weight to obtain a biochar precursor;
[0058] (3) placing the biochar precursor obtained in step (2) in a tubular furnace, heating it to 700° C. at a rate of 5° C. / min in a nitrogen atmosphere, carbonizing it at this temperature for 2 h, and naturally cooling it to room temperature to obtain nano zero-valent iron biochar;
[0059] (4) The nano-zero-valent iron biochar was immersed in a 0.2 mol / L sodium sulfide nonahydrate solution, heated at 60°C for 60 min, and the precipitate was obtained by centrifugation. The precipitate was dried to constant weight to obtain sulfur-doped nano-zero-valent iron biochar, which was recorded as FCS.
[0060] Comparative Example 5:
[0061] (1) 5 g corn stalks (40-100 mesh) were added to 100 mL of 1 mol / L sodium hydroxide solution, and heated in a constant temperature oil bath at 120° C. at normal pressure for 2 h. The pulping black liquor was obtained after solid-liquid separation by vacuum filtration.
[0062] (2) Take 20 mL of the pulping black liquor obtained in step (1), add ferric chloride hexahydrate thereto, the concentration of ferric chloride hexahydrate added is 0.46 mol / L, react at 60° C. for 60 min, wash and centrifuge the precipitate after centrifugation three times, and then freeze-dry it as the raw material for preparing subsequent biochar.
[0063] (3) soaking the biochar precursor obtained in step (2) in a 0.2 mol / L sodium sulfide nonahydrate solution, heating the mixture at 60° C. for 60 min, centrifuging the mixture to obtain a precipitate, washing the precipitate three times with ultrapure water, and drying the precipitate to a constant weight to obtain a sulfur-doped biochar precursor;
[0064] (4) The precipitate obtained in step (3) was pyrolyzed at 700° C. for 2 h in a tube furnace and naturally cooled to room temperature to obtain sulfur-doped iron-based biochar, which was recorded as FSC.
[0065] The residual lignin concentration and residual iron ion concentration of the supernatant 0.40F, 0.46F, 0.55F and 0.65F obtained from the first centrifugation in Example 1-2 and Comparative Example 1-3 were tested, and the results were as follows: Figure 2 Attached Figure 1It is shown that as the concentration of ferric chloride added increases, the remaining lignin gradually decreases and is lower than the remaining lignin concentration after the traditional acid precipitation (Comparative Example 1). Compared with the traditional method, the lignin removal rate is increased by 10.9%, 64.43%, 78.48% and 88.29%, respectively. This result shows that the method of the present invention has a high efficiency of lignin recovery. Figure 2 The results show that the added ferric chloride reacted with the original solution and formed a precipitate. The concentration of the remaining iron ions in the liquid after precipitation was much lower than the concentration of the iron ions initially added. The utilization rates of the ferric chloride in the remaining liquid at 0.40F and 0.46F were as high as 99.55% and 97.02%, respectively.
[0066] The yields of the four biochars prepared in Examples 1-2 and Comparative Examples 2-3 were tested respectively. The results are as follows: Figure 3 As shown in the attached figure, the yields of the four biochars are 65.45%, 71.82%, 68.93% and 61.82% respectively. The biochar raw material with the highest yield comes from the precipitate obtained by adding 0.46 mol / L ferric chloride.
[0067] XPS test was performed on the chemical element composition of the biochars prepared in Examples 1-2 and Comparative Examples 1-3. The results are as follows: Figure 4 As shown in the attached figure, compared with the biochar LC made from traditionally extracted lignin, the carbon content on 0.40FLC, 0.46FLC, 0.55FLC and 0.65FLC is significantly increased, from 36.69% to 49.23%, 66.71%, 66.65%, 66.95%, respectively. The high carbon content undoubtedly comes from the sedimentation of lignin in the stock solution. This result further confirms the claim that the method of the present invention has a higher recovery rate for lignin. At the same time, the iron content in 0.46FLC is 8.11%, which is not much different from 0.55FLC and 0.65FLC. Figure 2 and Figure 3 The results showed that the dosage of 0.46 mol / L ferric chloride was the optimal condition for lignin recovery and biochar preparation.
[0068] The four biochars prepared in Examples 1-2 and Comparative Examples 2-3 were further subjected to XRD tests to determine their phase compositions. Figure 5 As shown in the attached figure, 0.40FLC, 0.46FLC, 0.55FLC and 0.65FLC all contain FeS and Fe 2 (SiO 4 ) two phases, in addition, the presence of zero-valent iron was detected in 0.40FLC and 0.46FLC.
[0069] Based on the above results, it can be confirmed that 0.46 mol / L is the optimal iron ion concentration for recovering lignin, and 0.46 FLC is the best sulfur-doped zero-valent iron biochar prepared by the method of the present invention. A high-resolution TEM test was performed on the 0.46 FLC obtained in Example 2 to determine that the zero-valent iron particles were nanometer-sized. Based on the above facts and results, the feasibility of the present invention in the method of efficiently recovering lignin to prepare sulfur-doped nano zero-valent iron biochar was confirmed.
[0070] XRD tests were performed on the biochars obtained in Comparative Example 4 and Comparative Example 5, and the results are as follows: Figure 7 and Figure 8 Attached Figure 7 It shows that the biochar obtained by treating the black liquor of biomass with sodium hydroxide is first precipitated with ferric chloride and then immersed in sodium sulfide again, and only the biochar with zero-valent iron phase as the main phase can be obtained. Furthermore, the chemical element composition of XPS is C (68.92%), O (21.23%), Fe (8.78%), S (1.07%), which confirms that the sulfur element is loaded on the biochar, but it cannot be presented on the surface of the material in the form of crystals. Figure 8 It shows that the black liquor obtained by treating it with sodium hydroxide is first precipitated with ferric chloride, and then the precipitate is dried and soaked in sodium sulfide again. The obtained dry body is carbonized to produce biochar with ferrosoferric oxide as the main phase. Although zero-valent iron, ferrous sulfide and iron disulfide phases appear, its strength is obviously insufficient compared with Example 1-2.
[0071] Application Example: The steps of the method for degrading sulfonamide antibiotics by catalyzing peroxymonosulfate using the six biochars prepared in Examples 1-2 and Comparative Examples 2-5 are as follows:
[0072] Two catalytic degradation systems were formed using 0.4 g / L of six sulfur-doped iron-based biochars obtained from Examples 1-2 and Comparative Examples 2-5, 1 mmol / L potassium persulfate, and 10 mg / L sulfamethoxazole and sulfadimethoxine, respectively. The residual concentrations of sulfamethoxazole and sulfadimethoxine were measured at certain time intervals to determine the catalytic ability of the biochar.
[0073] like Fig. 9 As shown in the figure, the results show that with the participation of 0.40FLC, 0.46FLC, 0.55FLC, 0.65FLC, FCS and FSC, the degradation efficiency of sulfamethoxazole reached 66.84%, 71.00%, 74.52%, 79.03%, 23.09% and 29.70% at 1 min, and the final degradation effect at 60 min was 95.04%, 95.81%, 95.72%, 96.71%, 62.71% and 70.67%, respectively. In addition, as Fig.10As shown, with the participation of 0.40FLC, 0.46FLC, 0.55FLC, 0.65FLC, FCS and FSC, the degradation efficiency of sulfadimethoxine reached 75.31%, 80.15%, 82.20%, 84.97%, 20.29% and 28.08% respectively at 1 minute. The final degradation effects of 60 minutes were 99.77%, 99.59%, 99.30%, 99.36%, 77.94% and 86.91% respectively. According to the above results, it is shown that the four biochars of the present invention show efficient catalytic degradation ability for the two antibiotics in the advanced oxidation system with potassium persulfate. The comprehensive comparison with the degradation results of the comparative example shows that the catalytic performance of the biochar obtained by the method of the present invention is very excellent and can be applied to the field of water treatment.
[0074] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for efficiently preparing biochar with high catalytic performance based on pulping black liquor, characterized in that: The method: S1: placing the waste biomass in a mixed solution of sodium hydroxide and sodium sulfide and heating it at high temperature to separate the solid and liquid to obtain black liquor; S2: Add ferric chloride hexahydrate to the black liquor, heat for reaction, freeze-dry the precipitate after centrifugation, and then pyrolyze it at high temperature in a tubular furnace to obtain sulfur-doped nano zero-valent iron biochar.
2. The method according to claim 1, characterized in that The waste biomass in S1 is straw, wood or livestock and poultry manure, the concentration of sodium hydroxide in the mixed solution is 0.5-1.5 mol / L, the molar ratio of sodium hydroxide to sodium sulfide is (4-6):1, and the ratio of waste biomass to mixed solution is 1 g: (15-25) mL.
3. The method according to claim 1, characterized in that: The high temperature heating temperature in S1 is 110-130°C and the time is 1.5-2.5h.
4. The method according to claim 1, characterized in that: The concentration of ferric chloride hexahydrate in the black liquor in S2 is 0.4-0.5 mol / L.
5. The method according to claim 1, characterized in that The heating temperature in S2 is 50-70°C, the time is 0.5-1.5h, and the high temperature pyrolysis temperature is 650-750°C, the time is 1-3h.
6. Use of the method according to any one of claims 1 to 5 in high-value conversion of kraft pulping black liquor.
7. Sulfur-doped nano zero-valent iron biochar prepared by the method described in any one of claims 1 to 5.
8. Application of the sulfur-doped nano zero-valent iron biochar according to claim 7 in the field of water treatment.
9. The method for catalytic degradation of antibiotic wastewater using biochar according to claim 7, characterized in that: The method: Sulfur-doped nano-zero-valent iron and peroxymonosulfate were added to antibiotic wastewater and treated at room temperature.
10. The method according to claim 9, characterized in that The antibiotics included sulfamethoxazole and sulfamethoxazole, the antibiotic concentration in the wastewater was 5-15 mg / L, and the biochar dosage was 0.35-0.45 g / L.
Citation Information
Patent Citations
Preparation method and application of biochar-loaded nano zero-valent iron sulfide material
CN110980858A
Preparation method, product and application of iron-loaded biochar
CN111604082A
Method for preparing magnetic biochar from waste biomass
CN112079342A
Method for preparing activated carbon loaded vulcanized nano zero-valent iron composite material by one-step method
CN114950357A
Method for low-temperature hydrophilic modification of lignin
CN115975216A